PEMANFAATAN KUNYIT (Curcuma longa Linn) UNTUK MEMERIKSA BORAKS PADA BEBERAPA JENIS MAKANAN YANG BEREDAR DI PASAR PEKANBARU - Eli Yusrita; Mega Pratiwi Irawan; Annisa Salsabila; Amanda Rizky Fadillah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Borax is an ingredient known to the pharmaceutical industry as a medicinal ingredient such as ointments, powders, compress solutions, oral ointments and eye washes. Borax is also a wood preservative and wood antiseptic. If borax is found in food, in the long term it will accumulate in the brain, liver, fat and kidneys. Use in large amounts can cause fever, depression, kidney damage, decreased appetite, indigestion, stupidity, confusion, skin inflammation, anemia, seizures, fainting and even death. The dangers of borax for the human body are widely known by the general public, however, not many people know how to detect it. Turmeric (Curcuma longa Linn) is a natural food coloring agent. The content of turmeric compounds consists of curcuminoids, bisdesmetoksicurcumen. To prove that turmeric can be used to detect the borax content in food, it is necessary to test. This study aims to determine whether turmeric can be used to detect borax in foodstuffs circulating in Pekanbaru traditional markets. This research is based on the nature of the problem is experimental, the research design used is a parallel design with matching. The sampling method used is purposive. Turmeric can be used as a test material for the presence of borax in food. Based on the qualitative test using three methods, it was found that there were several positive and negative samples and the three methods showed the same identification results.Keywords: Tumeric, Borax, Food